The Use of ICT to Improve Teachers' Skill in Language Learning in the Classroom - Rahman, O Suzana (Universitas Swadaya Gunung Jati, 2013)
The utilization of Information and Communication Technology (ICT) in language learning has been an important and interesting topic both among students and also teachers. there are some suggestions about what to prepare and what activities that can be conducted by teachers in the classroom, especially for teaching-learning of English language that can be applied for all subject. The use of ICT will not only improve teacher's skill, but it will also make teachers more creative in preparing the material that will be transferred to the students.